1999
DOI: 10.1128/jvi.73.2.1719-1723.1999
|View full text |Cite
|
Sign up to set email alerts
|

T134, a Small-Molecule CXCR4 Inhibitor, Has No Cross-Drug Resistance with AMD3100, a CXCR4 Antagonist with a Different Structure

Abstract: T22, an analog of polyphemusin II (18 amino acid residues), was found to block T-tropic human immunodeficiency virus type 1 (HIV-1) entry into target cells as a CXCR4 inhibitor. We synthesized T134, a small analog (14 amino acid residues) of T22 with reduced positive charges. T134 exhibited highly potent activity and significantly less cytotoxicity in comparison to that of T22. T134 prevents the anti-CXCR4 monoclonal antibody from binding to peripheral blood mononuclear cells but has no effect on the binding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(33 citation statements)
references
References 31 publications
0
32
0
1
Order By: Relevance
“…It has been also shown, especially in the case where the HIV‐1 virus uses CXCR4 as coreceptor that the electrostatic interactions between the charged amino acids of CXCR4 and the V3 region of gp120 are of vital importance for viral entry. This type of interactions has been reported to be crucial for the anti‐HIV‐1 activity that is exhibited by molecules as the T22, T140 and their derivatives 41–44. Authors of this paper have characterized the CCR5Nt—V3 peptides interaction with surface plasmon resonance, light scattering and molecular modeling analyses12, 14, 16, 18 and have shown that electrostatic interactions are the main type of interaction occurring between the peptides.…”
Section: Discussionmentioning
confidence: 94%
“…It has been also shown, especially in the case where the HIV‐1 virus uses CXCR4 as coreceptor that the electrostatic interactions between the charged amino acids of CXCR4 and the V3 region of gp120 are of vital importance for viral entry. This type of interactions has been reported to be crucial for the anti‐HIV‐1 activity that is exhibited by molecules as the T22, T140 and their derivatives 41–44. Authors of this paper have characterized the CCR5Nt—V3 peptides interaction with surface plasmon resonance, light scattering and molecular modeling analyses12, 14, 16, 18 and have shown that electrostatic interactions are the main type of interaction occurring between the peptides.…”
Section: Discussionmentioning
confidence: 94%
“…The CXCR4 inhibitor, AMD-3100, blocks HIV-1 entry and inhibits binding of SDF1-a to CXCR4 [114]. Other small molecule inhibitors that block T-tropic HIV-1 have been identified, such as ALX40-4C T22, T134, and T140 [115]. The blocking of CCR5 and CXCR4 could result in selective pressures, which lead HIV-1 to switch to use alternative coreceptors that may be highly beneficial to the virus.…”
Section: O R E C E P T O R I N H I B I T O R Smentioning
confidence: 99%
“…Die Substanzen T134 und AMD3100 wurden als blockierende Antagonisten für den CXC-Chemokinrezeptor CXCR4 beschrieben. Sie blockieren die Bindung eines gegen den CXCR4 gerichteten monoklonalen Antikörpers und verhindern den CXCR4 vermittelten HIV-Eintritt [34]. In weiteren Studien wurden klein-molekülige Chemokinrezeptor-Antagonisten, die gegen den CC-Chemokinrezeptor CCR1 gerichtet waren, untersucht.…”
Section: Die Bedeutung Des Chemokinrezeptors Ccr3unclassified